2003
DOI: 10.1139/s03-028
|View full text |Cite
|
Sign up to set email alerts
|

Release of arsenic and molybdenum by reductive dissolution of iron oxides in a soil with enriched levels of native arsenic

Abstract: This study examined the release of arsenic (As), molybdenum (Mo), and iron (Fe) into the aqueous phase during reductive dissolution of iron oxides in an amended acid sulfate soil naturally enriched in arsenic. These acid sulfate soils occur worldwide and have a significant distribution in parts of Alberta and British Columbia. Reactions were studied in incubation vessels under controlled laboratory conditions. Soils were driven anaerobic by stimulation of indigenous bacteria using a glucose addition and then p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…Stock solutions were either autoclaved or sterilely filtered and stored in serum bottles under N 2 . Solutions of sodium thiosulfate pentahydrate (Na 2 O 3 S 2 · 5H 2 O), sodium sulfite (Na 2 SO 3 [anhydrous]; Fluka), potassium tetrathionate (K 2 S 4 O 6 ; Sigma-Aldrich), sodium sulfide nonahydrate (Na 2 S · 9H 2 O; Sigma-Aldrich), and potassium polysulfide (K 2 S x ; Sigma-Aldrich) were prepared in ultrapure water. The latter two were prepared inside a Coy anoxic glove box (N 2 -H 2 [95/5, vol/vol]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stock solutions were either autoclaved or sterilely filtered and stored in serum bottles under N 2 . Solutions of sodium thiosulfate pentahydrate (Na 2 O 3 S 2 · 5H 2 O), sodium sulfite (Na 2 SO 3 [anhydrous]; Fluka), potassium tetrathionate (K 2 S 4 O 6 ; Sigma-Aldrich), sodium sulfide nonahydrate (Na 2 S · 9H 2 O; Sigma-Aldrich), and potassium polysulfide (K 2 S x ; Sigma-Aldrich) were prepared in ultrapure water. The latter two were prepared inside a Coy anoxic glove box (N 2 -H 2 [95/5, vol/vol]).…”
Section: Methodsmentioning
confidence: 99%
“…Potentially toxic trace metalloids and metals such as arsenic, lead, and cadmium sorb to the surface of iron(III) (oxyhydr)oxides and are removed from the aqueous phase (1)(2)(3)(4)(5). Also, the availability of nutrients such as phosphate can be limited by adsorption (6,7).…”
mentioning
confidence: 99%
“…Weaker Fe(II) bonds enhance reductive dissolution and release of species from oxides surfaces. For example, in Alberta (Canada) microbial activity in acid sulphate soils released significant amounts of As when the Eh was below +100 mV [23]. Mine tailings at the former Delnite gold mine in Northern Ontario showed that As(V) reduction and mobilization occurred due to reductive dissolution of goethite, influenced by a biosolid-cover [24].…”
Section: Introductionmentioning
confidence: 99%
“…Although the study area is semi urban but surroundings are agricultural sites hence the nutrients leaching from fertilizer input in groundwater of study area is obvious. The strong loading of As and Fe is clear evidence of reductive dissolution of iron oxyhydroxide (FeOOH) which is widely believed mechanism of arsenic release in Holocene alluvial aquifers of the world (Smedley & Kinniburgh, 2002;Chatain et al, 2005;Bennett & Dudas, 2003). Due to high affinity of As for iron oxides, arsenic concentrations in natural ferrihydrite samples have been documented with values up to 14 wt% As (Rancourt et al, 2001).…”
Section: Principle Component Analysis (Pca)mentioning
confidence: 99%